A importância da matemática no desenvolvimento da astronomia - Rodas Neto, Humberto Ferreira (2016)
This paper deals with the way astronomy has developed and the importance of mathematics in this evolution. The need to understand phenomena around them, made the primitive man was interested in astronomy. In that sense, astronomy is often regarded as the oldest of the sciences. There are records that the Babylonians, Chinese, Assyrians and Egyptians, around 3000 BCE, already dealt with this matter. These studies had practical goals, such as predicting the best time for planting and harvesting, measuring the passage of time. One of the summits of ancient astronomy took place in Greece in 600 BCE to 400 dEC. The geocentric idea, which consisted of the earth as the center of the universe, was dominant in society at this time. This idea fell by Earth in mid-sixteenth century when the Polish Nicolaus Copernicus published a book defending the Heliocentric theory, beginning what would be the new astronomy. Kepler to study the particularities of Mars described mathematical laws for the movements of the planets, as well as the perception of their elliptical orbits, while Newton proposed a relationship between the attractive forces between the bodies to their masses and the distance between them called the Law of Universal Gravitation. In this sense, mathematics was a major tool for these theories firmassem. With discoveries about space and time in his Theory of Relativity, Einstein proposed in 1915, the general theory of relativity which is the generalization of Newton's gravitational theory. Such a theory opened new horizons for the study of the heavens. Therefore, it is extremely important to know the historical part of the Astronomy and the role of mathematics in the process.